SUPERVISORS’ PERCEPTION OF RECORD MANAGEMENT PRACTICES BY SECRETARIES IN COLLEGES OF EDUCATION IN SOUTH EAST NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
This study examined supervisors’ perception of record management practices by secretaries incolleges of education in South East Nigeria. Two research questions guided the study while threenull hypotheses were tested. This study adopted a descriptive survey research design. Thepopulation of this study consisted of 107 supervisors from seven colleges of education in SouthEast Nigeria. The entire population of 107 supervisors from colleges of education in in SouthEast Nigeria was used as sample for this study. Therefore, there is no sampling for the studysince the population is of a manageable number. The instrument was titled “RecordsManagement Practices Questionnaire (RMPQ)”. The instrument was subjected to face validationdone by three experts. Cronbach Alpha was used to determine the internal consistency of theinstrument. An overall co-efficient of 0.83 was obtained. The researcher personally administeredthe questionnaire to the respondents in their offices with the help of four research assistants whowere briefed by the researcher on what to do. Mean and standard deviation were statistical toolsused to answer the research questions while t-Test of independence was used to test the nullhypotheses at 0.05 alpha level. The findings revealed that supervisors agreed on record creationpractices while they disagreed on record storage practices and record maintenance practices ofsecretaries in colleges of education in South East Nigeria. The findings also revealed that there isno significant difference in the mean ratings of supervisors on record creation practices andrecord storage practices, record maintenance practices of secretaries in colleges of education inSouth East Nigeria based on their years of experience and gender. Based on these findings, itwas recommended amongst others that secretaries in colleges of Education in South East Nigeriashould enrol in workshop training programmes to acquire relevant records managementpractices.
Keywords: Supervisors, secretaries, record, record management.